A Molecular Analogue of the C−H Activation Intermediate of the Silica‐Supported Ga(III) Single‐Site Propane Dehydrogenation Catalyst: Structure and XANES Signature. Issue 7 (22nd June 2021) - Rochlitz, Lukas; Searles, Keith; Nater, Darryl F.; Docherty, Scott R.; Gioffrè, Domenico; Copéret, Christophe
Abstract: Propane dehydrogenation is an important field of research due to an increasing world‐wide demand of propene while classical production routes through naphtha cracking are in decline. In that context, silica‐supported Ga(III) sites, synthesized from surface organometallic chemistry principles, show high selectivity and stability in the propane dehydrogenation reaction. This performance is in significant contrast to the reported fast deactivation and lower selectivity of most Ga2 O3 and CrO3 based materials. The Ga‐catalyzed propane dehydrogenation reaction is proposed to proceed through the formation of Ga alkyl intermediates for which it would be desirable to have detailed structural and spectroscopic information. Here, we prepare a consistent series of Ga(III) molecular complexes with varying numbers of alkyl and siloxide ligands; they are characterized by single crystal X‐Ray diffraction and X‐Ray Absorption Near Edge Structure analysis, which is known to be highly sensitive to the Ga coordination environment. We report in particular the structure and the spectroscopic signatures of [Ga( i Pr)(OSi(O t Bu)3 )2 (HOSi(O t Bu)3 )], a molecular mimic of the key proposed reaction intermediates in the Ga‐catalyzed PDH reaction. Abstract :